Parametric Based Techno‐Economic Evaluation for a Solar Thermal‐PV Integrated Multi‐Commodity Storage Facility - Malik Shahzaib (22504349) (2024)
Postharvest losses and spoilage of agricultural products are a major problem for tropical countries, and it is even more challenging for countries encountering fluctuating power shortages, such as Pakistan. Therefore, this study focused on the energy and economic analysis of cold storage to store three products (potatoes, pomegranates, and potatoes) according to the season and storage span throughout the year. The cooling load of the cold store was supported by a LiBr‐H2O vapor absorption and vapor compression refrigeration system to maintain the desired temperature for each product during cold storage. A solar thermal PV system is installed to operate cold storage refrigeration systems. Cold storage performance was analyzed by developing thermal models of integrated systems using the ambient conditions of Lahore, Pakistan. A parametric study was also conducted to analyze the impact of various working parameters on integrated system performance, and it was found that the maximum peak cooling load of 91 kW inside cold storage is attributed to pomegranates owing to high ambient conditions during its loading month. The product loading rate significantly affects the cooling load of cold storage and varies directly with it, as observed for an increase in the product loading rate from 0 to 50 000 kg/day cooling load also increases from 34 to 87 kW. To meet the thermal demand of the generator of the vapor absorption system, parabolic troughs were installed to operate cold storage, and it was found that a minimum of four PTC were needed to support the peak cooling load at the maximum product loading rate and minimum DNI value. To meet the electrical demand of cold storage electrical equipment and the compressor of the vapor compression system, solar photovoltaic panels were installed, and it was found that a minimum of 618 panels was required at a minimum tilted radiation value. To validate the viability of proposed design system economic analysis was also conducted which revealed a payback period of 12 years for Kinnow and potatoes and 16 years for pomegranates. Other Information Published in: Energy Storage License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/est2.70022